2011
DOI: 10.1007/s00066-011-2272-0
|View full text |Cite
|
Sign up to set email alerts
|

Procedure for creating a three-dimensional (3D) model for superficial hyperthermia treatment planning

Abstract: Using the final procedure to obtain a patient- and treatment-specific CT scan, it is possible to create a 3D model for SHTP.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 42 publications
0
4
0
Order By: Relevance
“…The hyperthermia group in Rotterdam reported that the Rotterdam method detailed a hyperthermia treatment planning system for which they calculated specific absorption rate (SAR) distributions and the successful outcomes of hyperthermia in patients with cervical cancer. They also reported that areas of pain correlated with modelled SAR peak locations [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…The hyperthermia group in Rotterdam reported that the Rotterdam method detailed a hyperthermia treatment planning system for which they calculated specific absorption rate (SAR) distributions and the successful outcomes of hyperthermia in patients with cervical cancer. They also reported that areas of pain correlated with modelled SAR peak locations [9][10][11][12][13][14][15].…”
Section: Discussionmentioning
confidence: 99%
“…A computer tomography (CT) scan in identical position as during SHT was made for all 40 patients after the placement of invasive thermometry catheters [15]. Figure 3 shows an example of CT slice segmented into muscle, fat, lung, bone and tumour using iSeg (v 3.5, Zurich MedTech, Switzerland).…”
Section: ) Patient Specific 3d Modelsmentioning
confidence: 99%
“…For patient-specific hyperthermia treatment planning a different approach is required to model the treatment position, orientation and the treatment curvature of the applicator. Linthorst et al described a procedure to create a model for superficial hyperthermia with rigid Lucite cone applicators, using a mold representing the antenna footprint on the CT scan [22]. Drizdal et al have developed a method to reconstruct the position of an array of six Lucite cone applicators from multiple-view images [23].…”
Section: Introductionmentioning
confidence: 99%